2016
DOI: 10.3390/ijms17030356
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Long Noncoding RNAs and MicroRNAs in Health and Disease

Abstract: Abstract:Protein-coding genes account for only a small part of the human genome; in fact, the vast majority of transcripts are comprised of non-coding RNAs (ncRNAs) including long ncRNAs (lncRNAs) and small ncRNAs, microRNAs (miRs). Accumulating evidence indicates that ncRNAs could play critical roles in regulating many cellular processes which are often implicated in health and disease. For example, ncRNAs are aberrantly expressed in cancers, heart diseases, and many other diseases. LncRNAs and miRs are there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(152 citation statements)
references
References 87 publications
4
148
0
Order By: Relevance
“…It has been demonstrated that miRNAs can be downregulatedted through complementing with long noncoding RNAs (lncRNAs) (12). In this study, we found a negative relationship between long noncoding RNA TUG1 (lncRNA-TUG1) and miR-381 in GC tissues (P<0.01, Fig.…”
Section: Mir-381 Was Negatively Regulated By Long Noncoding Rna Tug1mentioning
confidence: 60%
See 1 more Smart Citation
“…It has been demonstrated that miRNAs can be downregulatedted through complementing with long noncoding RNAs (lncRNAs) (12). In this study, we found a negative relationship between long noncoding RNA TUG1 (lncRNA-TUG1) and miR-381 in GC tissues (P<0.01, Fig.…”
Section: Mir-381 Was Negatively Regulated By Long Noncoding Rna Tug1mentioning
confidence: 60%
“…However, the expression and functions of miR-381 in gastric carcinoma are still unclear. Recently, long noncoding RNAs (lncRNAs) were found to act as a sponge of microRNAs and regulate the expression and function of microRNAs (12), but there is still no study to investigate whether miR-381 can be regulated by lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…These RNAs may work in gene regulatory networks as signals, decoys, guides or scaffold [46][47][48], and coordinate histone modifications by binding to various histone modification enzymes such as PRC2, which is a methyltransferase for H3K27me3 and is involved in the repression of gene transcription [49][50][51]. EZH2 is a catalytic subunit of PRC2 [52].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been considered as oncogenes or tumor suppressors by regulating cell proliferation and differentiation [20]. The crosstalk between lncRNAs and miRNAs has been reported to control cancer progression [21]. miR-203a has been found to be a crucial regulator involved in various cancers, such as gastric cancer [22], nasopharyngeal carcinoma [23], breast cancer [24], lung cancer [25], live cancer [26], and CRC [27].…”
Section: Introductionmentioning
confidence: 99%